2010
DOI: 10.1002/pssb.200983960
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of La0.67Sr0.33MnO3 monolayers grown by pulsed laser deposition

Abstract: Integration of functional oxides on silicon is a key issue for the development of oxide-based electronics. For this purpose, monitoring the growth of these materials by an in situ technique becomes essential to control the thickness, the roughness and the oxidation state of the layers. Using a new static optical setup, i.e. with no modulation, we have studied the deposition and the annealing of pulsed-laser deposited La 0.67 Sr 0.33 MnO 3 monolayers on pseudosubstrates SrTiO 3 (100)/Si at high temperature. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Typically connected to the PLD chamber, RHEED systems are often equipped with a differentiated vacuum pumping unit for in situ observations during thin-film deposition under a gaseous ambience [10]. Several other in situ characterization techniques, including low-energy electron diffraction, X-ray photoelectron spectroscopy, Auger electron spectroscopy, coaxial impact collision ion scattering spectroscopy, scanning probe microscope, and optical measurements, such as spectroscopic ellipsometry, have also been implemented in PLD systems [13][14][15][16][17]. Laser molecular beam epitaxy (MBE) (Figure 8.2) [11,12], which couples in situ RHEED observation with PLD for epitaxial growth, has proved to enable real-time growth control at an atomic-layer scale.…”
Section: Monitoring and Diagnostic Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically connected to the PLD chamber, RHEED systems are often equipped with a differentiated vacuum pumping unit for in situ observations during thin-film deposition under a gaseous ambience [10]. Several other in situ characterization techniques, including low-energy electron diffraction, X-ray photoelectron spectroscopy, Auger electron spectroscopy, coaxial impact collision ion scattering spectroscopy, scanning probe microscope, and optical measurements, such as spectroscopic ellipsometry, have also been implemented in PLD systems [13][14][15][16][17]. Laser molecular beam epitaxy (MBE) (Figure 8.2) [11,12], which couples in situ RHEED observation with PLD for epitaxial growth, has proved to enable real-time growth control at an atomic-layer scale.…”
Section: Monitoring and Diagnostic Toolsmentioning
confidence: 99%
“…The crystal orientation of the films depended on the background and nitrogen partial pressures as well as growth temperature. TEM observations also revealed that in-plane AlN jj [11][12][13][14][15][16][17][18][19][20] sapphire and [11][12][13][14][15][16][17][18][19][20] AlN jj [11][12][13][14][15][16][17][18][19][20] 6H-SiC were epitaxial relationships between AlN and substrate materials, respectively. Figure 8.17 shows X-ray diffraction scans of AlN films grown on sapphire (0001) and 6H-SiC (0001).…”
Section: Aluminium Nitridementioning
confidence: 99%
“…In order to investigate the epitaxial mechanism of perovskite film growth on buffer-layered silicon substrate and to clarify how the buffer layers affect the film properties, we have realized the growth of two different functional oxide films on the STO/Si template by two different epitaxy reactor. Firstly 50 nm-thick LSMO films were grown by Pulsed Laser Deposition (PLD) [16]. Secondly 40 nm-thick BTO films were grown using MBE system.…”
Section: Epitaxy Of Strontium Titanate On Siliconmentioning
confidence: 99%
“…3 As of yet, researchers know very little about how complex interfacial phenomena between layers of the film affect magnetic properties. 1,[6][7] It is necessary to understand how local types of interference at layer boundaries including diffusion of chemical species, deviations from stoichiometry, and lattice mismatch resulting from different lattice parameter between the FM and AFM layer effect bilayer properties in order to fully characterize these heterostructures and utilize them in novel technologies. 6,7 This paper reports on experiments to determine how varying bilayer parameters effect interfacial interactions.…”
Section: Midterm Reportmentioning
confidence: 99%